Método para incrementar la sensibilidad diagnóstica del gammagrama óseo. - Jaramillo-Núñez, A.; Gómez-Conde, J. C. (Anales de Radiologia, Mexico)
Introduction: When interpreting bone scans, attimes it can bedifficult to reach an accurate diagnosis, mainly when seeking to distinguish marker accumulation is due to inflammation, infection, or early stage bone metastasis. This article shows how using computer programs substantially improves viewing of bone scans, allowing us to observe areas of marker accumulation which do not correspond to metastasis. Objective: Help reduce the number of false positives obtained when analyzing bone scans and increase their diagnostic sensitivity. Material and methods: We analyzed 11 bone scans taken from an equal number of men with problems of prostate cancer, between 23 and 87 years of age. To better view the digitalized bone scans, a Gaussian Alter was applied before the analysis, which substantially reduced image noise. Then shades of gray in the bones were analyzed, in both anterior and posterior bone scans, and tables were constructed with the values obtained. In particular the values obtained for the skull were analyzed in detail. Discussion: The results obtained suggest that it is possible to differentiate metastasis from other bone disease; however, for the technique to be efficient in searchingfor degenerative changes, infections, and fractures, a program needs to be implemented which performs the required tasks automatically given that, as currently performed, the process is very time consuming. Conclusion: The value of the shades of gray in the image are a function of the state of bone health: values on the order of 15 correspond to healthy bone for the cases analyzed, whereas values above 20 indicate that the patient has bone disease. We consider both the maximum and minimum values of shades of gray and the distribution of pixels with enhanced shades indispensable to determine the type of bone disease observed in a scan.